FORMATION OF TRADITIONAL PERFORMANCE SKILLS IN STUDENTS THROUGH VOCAL EXERCISES - Khamrokulov Naimdjon Bakhronovich (American Journals, 2025)
This article talks about the exercises conducted in cooperation with practical and theoretical knowledge in the processes of formation of performance skills of future specialists of vocal art, the results of practical work and solutions to scientific problems that arose as a result of analysis.
Keywords: Vocal art, pedagogue, performer, practical and theoretical knowledge, scientific analysis, performance skills.